2011
DOI: 10.1111/j.1467-789x.2010.00832.x
|View full text |Cite
|
Sign up to set email alerts
|

Acylation stimulating protein: a female lipogenic factor?

Abstract: Acylation stimulating protein (ASP) is a potent lipogenic factor produced from adipocytes. Plasma ASP levels were shown to increase in obesity, diabetes mellitus type II and dyslipidemia, and decrease after weight loss and fasting. Growing evidence suggests that ASP may significantly contribute to subcutaneous fat storage in females. In vitro, ASP stimulated triglyceride synthesis to a larger extent in subcutaneous compared with omental adipocytes. The ASP receptor binding affinity to plasma membranes prepared… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 86 publications
0
25
0
Order By: Relevance
“…Furthermore, functional studies showed that ASP-mediated triglyceride synthesis was markedly lower in omental adipocytes compared to subcutaneous adipocytes [30]. In vivo studies showed a decreased response to ASP-mediated triglyceride clearance in males compared to females in humans and mice [31]. …”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, functional studies showed that ASP-mediated triglyceride synthesis was markedly lower in omental adipocytes compared to subcutaneous adipocytes [30]. In vivo studies showed a decreased response to ASP-mediated triglyceride clearance in males compared to females in humans and mice [31]. …”
Section: Discussionmentioning
confidence: 99%
“…The purpose of this second estrous is unclear, but it may be involved in preliminary follicle development (the follicle is 'primed' and then arrested prior to entry into torpor). Alternatively, it has been hypothesized that the presence of the reproductive hormones progesterone and prolactin [which are typically considered lipogenic (reviewed in Saleh et al 2011)] allow pre-hibernatory females to build fat stores rapidly following the energetically expensive process of lactation (Strauss et al 2009). Similarly, in the arctic ground squirrel (U. parryii) androgen levels are elevated in the autumn during the prehibernation period.…”
Section: Interactions Between Sex Hormones and Food Intakementioning
confidence: 99%
“…Previous human studies have shown gender and regional differences in ASP levels and function (both binding and activity) in adipose tissue in mice and humans (reviewed by Saleh et al …”
Section: Introductionmentioning
confidence: 99%